BIOLOGI REPRODUKSI IKAN BELIDA (Chitala lopis) DI SUNGAI TULANG BAWANG, LAMPUNG - Limin Santoso (Berkala Perikanan Terubuk, 2009)
Knife fish (Chitala lopis) is one kind of freshwater fish of high economic value.Therefore the arrest activity continued and resulted in knife fish increasinglyscarce fish. The purpose of this study to determine the reproductive potential ofknife fish. Research carried out for four months in Tulang Bawang river,Lampung. Fish samples collected from the fisherman and gatherers along therivers. Observations were made include: morphology, length and weight, sexratio, gonado maturity level (GML), gonado somatic index (GSI) and fecundity.Total length of knife fish average 50,9 cm, 15,6 cm in height and weighing 883,90grams. Length and weight relationship is expressed by the equationW=0,0459L2,5005 which means that the type of fish growth is negative allometric.The number of knife fish more female than male, which sex ratio between malesand females 1 : 2,3. Most of the knife fish is immature gonads (GML I and II)with 0,35 gonado somatic index. Many knife fish immature gonads because thefish was not spawning season. Fecundity ranged of knife fish is 207-412 eggs oraverage of 290 eggs per fish.